2011
DOI: 10.1158/1541-7786.mcr-10-0449
|View full text |Cite
|
Sign up to set email alerts
|

The a3 Isoform Vacuolar Type H+-ATPase Promotes Distant Metastasis in the Mouse B16 Melanoma Cells

Abstract: Accumulating evidence indicates that the acidic microenvironments critically influence malignant behaviors of cancer including invasiveness, metastasis, and chemoresistance. Because the vacuolar-type H þ -ATPase (V-ATPase) has been shown to cause extracellular acidification by pumping protons, we studied the role of V-ATPase in distant metastasis. Real-time PCR analysis revealed that the high-metastatic B16-F10 melanoma cells strongly expressed the a3 isoform V-ATPase compared to the low-metastatic B16 parenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 51 publications
7
131
1
Order By: Relevance
“…Increased cancer cell invasive activity is frequently associated with aberrant V‐ATPase plasma membrane localization suggesting that increased acidification of the extracellular space plays an important role 29, 33, 34, 37, 47, 48, 49, 50, 51, 52…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased cancer cell invasive activity is frequently associated with aberrant V‐ATPase plasma membrane localization suggesting that increased acidification of the extracellular space plays an important role 29, 33, 34, 37, 47, 48, 49, 50, 51, 52…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…For example, using 2 closely related human breast cancer cell lines, MCF10a and MCF10CA1a, Capecci et al found that the levels of mRNA encoding V o a1 and V o a3 were highest in the invasive MCF10CA1a cells 48. Furthermore, the V o a3 isoform was also expressed in lung and bone metastasis of B16‐F10 cells, suggesting this isoform might be relevant to the increased metastatic potential of melanoma cells 51. As previously discussed, V o a isoforms can be expressed in a tissue‐enriched pattern and are associated with plasma membrane localization.…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…Specific inhibitors of V-ATPase are important because the enzyme is a potential therapeutic target in certain diseases, e.g., osteoporosis, deafness and cancer (Linnett and Beechey 1979;Farina and Gagliardi 1999;Bowman and Bowman 2005;Lu et al 2005;Morimura et al 2008;Otero-Rey et al 2008;Supino et al 2008;Hinton et al 2009;Perez-Sayans et al 2009;McHenry et al 2010;Nishisho et al 2011). The macrolide antibiotics concanamycin A and bafilomycin are the most potent and most selective inhibitors of V-ATPase, with IC 50 values down to the nM region (Bowman et al 1988;Farina and Gagliardi 1999;Gagliardi et al 1999;Huss et al 2002;Dixon et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, blocking V-ATPase activity inhibits pancreatic cancer cell invasion and reduces matrix metalloproteinase 9 activity (27). The highly metastatic mouse melanoma cell line B16-F10 expresses more a3 than the less metastatic B16 cell line (28). B16-F10 cells also localize V-ATPases to the plasma membrane, and knockdown of a3 suppresses invasion.…”
mentioning
confidence: 99%